ALBANIAN OPHIOLITES. I - MAGMATIC AND METAMORPHIC PROCESSES ASSOCIATED WITH THE INITIATION OF A SUBDUCTION - Bébien, Jean; Dimo-Lahitte, Ardiana; Vergély, Pierre; Insergueix-Filippi, Delphine; Dupeyrat, Laure (Ofioliti, 2000)
The Albanian ophiolite complexes, of Jurassic age, cover about 4,000 km2. They crop out as a NNW-SSE trending belt in the Mirdita tectonic zone. This belt shows a remarkable petrological diversity. Low- and very low-Ti magmatisms, particularly abundant to the East, seems to follow a high-Ti magmatism mainly located to the West. This diversity has been interpreted as a result of the original setting of these magmatic bodies: a mid-ocean ridge setting for the high-Ti magmatism, and a supra-subduction zone setting for the low- and very low-Ti magmatisms. Nevertheless, no break appears neither in magma compositions nor in space and time: the data support the hypothesis that Albanian ophiolites formed in a setting where both high-Ti, low-Ti and very low-Ti magmatims coexisted either spatially or temporally.The studies of the ophiolitic metamorphic sole can provide important information concerning this setting: a metamorphic sole, less than 0.5 km thick, occurs on both the eastern and western sides of the ophiolite belt. It mainly consists of amphibolites, gneisses and micaschists which grade rapidely downward into relatively unmetamorphosed rocks, and originates from high-Ti plutonic and volcanic rocks and from siliciclastic sediments. P-T conditions range from 800 to 850°C and 0.9-1.2 GPa in the granulite facies rocks, and from 300 to 400°C and 0.2-0.3 GPa in the greenschist facies rocks. According to 40Ar/39Ar geochronological data, magmatic samples from the ophiolites give ages indistinguisable from the age of the sole at the same latitude.An initiation of a subduction at or near a ridge can account for most of the previous observations. The high temperature-high pressure metamorphism observed in the infra-ophiolitic sole can be related to the subduction of a young, and still hot oceanic lithosphere at depth of at least 30 km. Dehydration ot this subducting lithosphere and release of H2O into a hot, refractory overlying mantle wedge can induce low- to very low-Ti magmatisms above the slab. High-Ti basalts would attest for the persistence of a residual spreading ridge magmatism. Therefore, the Albanian ophiolites probably bear witness to the metamorphic and magmatic processes related to an infant subduction zone. They suggest that high-Ti magmatisms showing a MORB affinity can be closely linked to lowto very low-Ti island-arc type magmatisms during the pre-arc stage, and they consequently present a significant opportunity for the investigation of supra-subduction zone ophiolites and fore-arc areas.